2018
DOI: 10.1186/s13046-018-0681-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: miR-3928v is induced by HBx via NF-κB/EGR1 and contributes to hepatocellular carcinoma malignancy by down-regulating VDAC3

Abstract: BackgroundHepatitis B virus (HBV) plays a critical role in the tumorigenic behavior of human hepatocellular carcinoma (HCC). MicroRNAs (miRNAs) have been reported to participate in HCC development via the regulation of their target genes. However, HBV-modulated miRNAs involved in tumorigenesis remain to be identified. Here, we found that a novel highly expressed miRNA, TLRC-m0008_3p (miR-3928v), may be an important factor that promotes the malignancy of HBV-related HCC.MethodsSolexa sequencing was applied to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…55,56 Based on previous reports, EGR1 also displays both facilitating and repressing effects in HCC. [26][27][28][29][30][31][32] For instance, EGR1 functions as an oncogene, promoting HCC growth and migration/invasion 27,29,31 and enhancing the drug resistance of HCC cells, likely through autophagy. 26 Conversely, EGR1 can inhibit HCC progression by repressing the EGFR-MAPK/AKT pathway 32 and promoting PTEN transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55,56 Based on previous reports, EGR1 also displays both facilitating and repressing effects in HCC. [26][27][28][29][30][31][32] For instance, EGR1 functions as an oncogene, promoting HCC growth and migration/invasion 27,29,31 and enhancing the drug resistance of HCC cells, likely through autophagy. 26 Conversely, EGR1 can inhibit HCC progression by repressing the EGFR-MAPK/AKT pathway 32 and promoting PTEN transcription.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] EGR1 plays complicated roles in HCC. Several studies have stated that EGR1 is overexpressed in HCC tissues, enhances drug resistance by promoting hypoxia-induced autophagy 26 and accelerates the progression of HCC; [27][28][29] however, data from several independent laboratories have demonstrated that EGR1 inhibits HCC cell motility and invasion. [30][31][32] In our present study, we found that CD24A was the predominant CD24 isoform in HCC and plays a major role in cell proliferation, migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Many oncogenes, growth factors, and tumor suppressor genes have been identified in processes of hepatocarcinogenesis 22 25 , however, the molecular carcinogenic mechanisms and the pathogenic biology of HCC remains unclear 22 , 26 – 28 . A growing amount of experimental evidence has been supporting a significant role for miRNAs in tumorigenesis of HCC 27 , 29 , 30 .…”
Section: Disscussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a subgroup of endogenous non-coding RNAs (ncRNAs) with 20~ 25 nucleotides in length and function by negatively regulating their target genes [ 9 ]. Accumulating evidence indicates that miRNAs can act as oncogenic or suppressive factors involved in the progression of HCC [ 10 12 ], and some even exhibit antitumor effects by regulating PPM1F expression. For example, miR-200c and miR-149 inhibit the invasion and metastasis in breast cancer and HCC by targeting PPM1F [ 13 , 14 ], but miR-590 has the tumor promoting effects in GC by targeting PPM1F [ 8 ].…”
Section: Introductionmentioning
confidence: 99%